Studi Pengaruh Suhu Kalsinasi terhadap Sintesis Katalis Asam Heterogen Zirkonia Tersulfatasi (So4/Zro2) dari Jenis Prekursor Zirkonium Oksida (Zro2) - Mega Fia Lestari (Indonesian Journal of Fundamental Sciences, 2018)
The 0.7 M SO4/ZrO2 catalyst was synthesized from the ZrO2 precursor with 0.7 M H2SO4 through the wet impregnation method, then examined the effect of calcination temperature (400 and 500 oC) on the catalyst through characterization using XRD, FT-IR, SEM-EDX, and acidity test using ammonia as the adsorbate base. The 0.7 M SO4/ZrO2-400 catalyst had two types of crystalline phases namely monoclinic and a small peak of metastable tetragonal, while the crystalline phase of 0.7 M SO4/ZrO2-500 was only monoclinic. The results of FT-IR analysis showed that the four typical bands of sulfate ions that were perfectly coordinated with zirconium cations were found both at 400 and 500 oC calcination temperatures with almost the same band intensity. However, the acidity test results showed that the 0.7 M SO4/ZrO2-400 catalyst had a total acidity that was slightly greater than 0.7 M SO4/ZrO2-500 which was 5.74 and 5.59 mmol g-1 respectively. The results of SEM-EDX analysis also showed that the surface of the 0.7 M SO4/ZrO2-400 catalyst was also brighter than 0.7 M SO4/ZrO2-500 which indicated that more sulfate ions were impregnated on the surface of zirconia with the SO3 species mass was 5.75% while the SO3 species mass of 0.7 M SO4/ZrO2-500 was only 4.62%.